(untitled) (Research, Society and Development, 2020)
Introduction: Drugs of plant origin have been used since ancient times. The use of medicinal plants in disease control has grown due to therapeutic feasibility and successful clinical cases. Some plant species are used to combat the symptoms caused by diabetes mellitus in association or not with traditional medicine, among them, the São Caetano melon (Momordica charantia L.). Objective: The objective of this literature review is to analyze the main researches on the use of M. charantia L. in the treatment of diabetes mellitus. Methodology: The work consists of an integrative literature review based on original articles in the English language from the Google Scholar, Oxford Academic, Science Direct, Taylor & Francis and Web of Science databases. Results: Of the 31 articles selected for the research, only 5 were used (16.13%). It was observed that in the 5 articles used, M. charantia L. reduced glycemic levels, as well as providing other benefits. Conclusion: The prophylactic use of M. charantia L. is an alternative in the treatment of diabetes mellitus, as well as other diseases.